Isolation and characterization of yeast from different sources - Sugarragchaa, Munkh-Erdene; Batjargal, Lhagvadolgor; Mijid, Narangerel; Battumur, Urantulkhuur (Mongolian Journal of Agricultural Sciences, 2020)
Four strains of yeasts isolated from some mare’s fermented milk, whey and fruit were identified using their morphology, biochemistry and phylogenetic characteristics. These yeasts belonged to four genera viz: Candida (one strain), Pichia (one strain), Saccharomyces (one strain) and Kluyveromyces (one strain). The physiological and biochemical tests of the yeasts carried out showed all isolates to ferment glucose for their growth. All isolates showed elliptical to round spores. Pichia kudriavzevii was able to ferment xylose of the four isolates. The assimilation and fermentation of most sugars by the isolates was variable. The blast sequence query showed that Saccharomyces cerevisiae and Pichia kudriavzevii had maximum identity (100%) with the genomic DNA sequence of MON-21 and MON-22, respectively at both ITS. Isolate Candida boidinii MON-23 was 100% homologous to Candida boidinii 18S rRNA gene sequence. The blast sequence query showed that Kluyveromyces marxianus MON-24 has the maximum identity (99%) with the genomic DNA sequence of Kluyveromyces marxianus at ITS 1 and ITS 4 sequence with that in the Genbank Library Database. Using MEGA 7 software, the phylogenetic trees were constructed to determine the evolutionary relationship of newly identified yeasts from our experiment and previously published yeast species. The sequences of the yeasts were deposited in the National Center for Biotechnology Information (NCBI) database. Ялгаатай эх үүсвэрээс ялгасан хөрөнгөнцрийн шинж чанар Монголчуудын эрт үеэс хэрэглэж ирсэн зарим уламжлалт исгэлэн бүтээгдэхүүн, сүү, сүүн бүтээгдэхүүний дайвар түүхий эд болох шар сүү, жимснээс хөрөнгөнцрийн цэвэр өсгөвөр ялган авч, тэдгээрийн морфологи, биохими, филогенетикийн шинж чанарыг судлав. МОН-21, 22, 23 болон 24 өсгөвөрүүд нь грам эерэг, эсийн урт нь 1.2-10.8 мкм, эсийн өргөн нь 0.5-6.0 мкм хэмжээтэй, пигмент үүсэлт нь цайвар шар өнгөтэй, жигд бөөгнөрсөн, дугуй, товгор хэлбэртэй, МОН-21 өсгөвөр нь нүүрстөрөгчийн эх үүсвэрээр галактоз, декстроз, МОН-22 өсгөвөр нь ксилоз декстроз, МОН-23 өсгөвөр нь сахароз, декстроз, ксилоз, фрюктоз, МОН-24 өсгөвөр нь мальтоз, ксилозыг тус тус ашиглаж чадахгүй байна. Дрожжийн ангилал зүйг ITS ген ашиглан тодорхойлоход, МОН-21 өсгөвөр нь Pichia kudriavzevii DGY49-тай 100%, МОН-22 нь Saccharomyces cerevisiae S5-тай 100%, МОН-23 өсгөвөр нь Candida boidinii NRRL Y-2332-тай 99.88%, МОН-24 өсгөвөр нь Kluyveromyces marxianus CCT 7735-тай 99.88% зүйлд тус тус ижил төсөөтэй байна. Мөн ITS1 болон ITS4 праймеруудыг ашиглан ялгасан өсгөвөрүүдийн зүйлийн генетик хамаарлыг тодорхойлоход, өсгөвөр МОН-23 болон МОН-24 нь бусад өсгөврүүдээс өөр хэмжээтэй буюу жижиг 18S рРНХ-ийн генийн молекултай, МОН-21 болон МОН-22 өсгөвөрүүд нь том 28S рРНХ-ийн генийн молекул хэмжээтэй байна. Эдгээр өсгөвөрүүдийг цаашид нарийвчлан судалж, исгэлтийн үйлдвэрлэлд ашиглах боломжтой хөрөнгө гарган авах, цэвэр өсгөврийн сан байгуулах, бүртгэлжүүлэх, дата мэдээлэл үүсгэх, үндэсний үйлдвэрлэлийг хөрөнгөөр хангах боломжийг нээж өгнө. Түлхүүр үг: хөрөнгөнцөр, kluyveromyces marxianus, рРНХ, pichia kudriavzevii, декстроз